Supera cognitive stimulation study with cognitively-unimpaired older adults: methodology and initial results of a randomized controlled clinical trial - Silva, Thais Bento Lima da; Ordonez, Tiago Nascimento; Santos, Gabriela dos; Costa, Laydiane Alves; Moreira, Ana Paula Bagli; Bacelar, Diana dos Santos; Souza, Maria Antonia Antunes de; Silva, Sabrina Aparecida da; Brucki, Sonia Maria Dozzi; Yassuda, Monica Sanches (Arquivos de Neuro-Psiquiatria, 2025)
Scientific investigations have highlighted the benefits of cognitive stimulation for cognitive, psychological, and social aspects in older individuals. However, there is a dearth of long-term, methodologically-rigorous studies. The aim of the present study was to describe the methods and the initial characteristics of the participants in a randomized controlled trial on cognitive stimulation. A total of 578 older individuals accepted invitations to participate in the study. Of these respondents, 362 met the eligibility criteria, and 255 were selected and randomized into the training, active control, and passive control groups. During the baseline stage (T0), 48 participants withdrew, resulting in a final T0 sample of 207 participants. The three groups were similar in terms of cognitive performance and sociodemographic and psychosocial variables, but they differed significantly regarding depressive symptoms, with the training group scoring higher. The methods herein described can help guide future research on cognitive stimulation in older adults.
Keywords: Cognition; Surveys and Questionnaires; Aged; Aging